Предмет: Алгебра,
автор: Аноним
х²-8(х-3)=24
(2х-1)(3х+1)+х(1-2х)=0
Ответы
Автор ответа:
0
1)раскрываем скобки
х²-8х+24=24
х²-8х=24-24
х²-8х=0
х(х-8)=0
х1=0 х-8=0
х2=8
2)раскрываем скобки и суммируем подобные члены
2х×3х+2х-3х-1+х-2х²=0
6х²-1-2х²=0
4х²=1
х²=1/4
х1=1/2. х2=-1/2
х²-8х+24=24
х²-8х=24-24
х²-8х=0
х(х-8)=0
х1=0 х-8=0
х2=8
2)раскрываем скобки и суммируем подобные члены
2х×3х+2х-3х-1+х-2х²=0
6х²-1-2х²=0
4х²=1
х²=1/4
х1=1/2. х2=-1/2
Похожие вопросы
Предмет: Русский язык,
автор: hey1pliz
Предмет: Биология,
автор: Dimsjsjd
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: svetlana198261
Предмет: Математика,
автор: хХхКаринахХх